Bright thermal (blackbody) emission of visible light from LnO2 (Ln = Pr, Tb), photoinduced by a NIR 980 nm laser. Issue 8 (15th January 2019) - Silva Filho, C. I.; Oliveira, A. L.; Pereira, S. C. F.; de Sá, Gilberto F.; da Luz, L. L.; Alves, S.
Abstract : The light-induced blackbody emission from lanthanide dioxide can improve the solar cell performance by converting NIR photons into bright visible light. Abstract : The increasing demand for renewable energy has been promoting a rapid development of photovoltaic technologies. Given this, photoinduced thermal emission is being explored with the aim of improving solar cell performance by converting low-energy IR photons into visible light. Here, we report the light-induced blackbody emission from LnO2 (Ln = Pr and Tb) as a potential emitter for thermophotovoltaic applications. Lanthanide dioxides display broad IR absorption and a direct optical band gap of 1.49 (PrO2 ) and 1.51 eV (TbO2 ). These materials achieve a maximum temperature of ∼1500 K under a power density excitation of 160 W cm −2 and display a stable bright light emission. Thermal emission can be tuned from laser power density modulation.